Estudos computacionais do modelo de mucina 2 e sua interação com quitosanas tioladas: uma nova estratégia para o estudo da mucoadesão e retenção de fármacos - Silveira, Cleverton Oliveira Cavalcanti da (2018)
Chitosans haveattractedinterest as a mucoadhesive excipient that increases the residence period of drugs along mucous membranes. The interaction with the mucin 2 throughout the intestine determines the level of mucoadhesion, potentiated with the insertion of thiolated substitutes in its structure. There were studies about the interactions between the glycoprotein mucin 2 and thiolated chitosans, ranking them based on the energy free of ligand-receptor complex interaction. The absence of in silicoworks in the study of mucoadhesion and the possible development of a methodology to this extent has motivated the investigation performed from the development of a mucin 2 model by the use of comparative modeling and fold recognition; molecular dynamics, docking and mmpbsa. When non-bonded interactions were considered, the Chitosan-N-acetyl cysteine (AC-Chi) ligand equaled itself in terms of energy free of bond to the hexamer Chitosan-thiobutylamidine (TBA-Chi) and the Unmodified Chitosan (U-Chi) displayed the second greatest ?G(binding).This result showed that the level of mucoadhesion of thiolated chitosans has assumed a diverse order, when considering only the non-binding interactions, different from the experimental results that do not allow a specification of the nature of the interaction involved in the process